Competition in two-sided market : with heterogeneous users and negative externalities. - Chen, Hongyu. (2013)
Social networking sites (SNS) like Facebook are fast becoming part of our daily lives. Increasingly, businesses and organizations are getting on this bandwagon as SNS have the ability to reach a large mass of the population and influence consumer behavior. Facebook reported annual revenue of US$5.1 billion in 2012 and boosts an active user population of more than 1 billion active users in 2012. The emergence of the SNS industry has large influence on every aspect of our society. Thus, it has attracted much academic attention, especially in social sciences. However, current papers do not consider heterogeneity and negative externality in the two-sided market modeling, which we first draw attention to these issues. This paper aims to study the market structure of the SNS industry and discuss the appropriate pricing strategies for the SNS firm.